PENGARUH ARUS KAS DAN RASIO HUTANG TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL MODERATING - Luayyi, Sri; Nurvianasari, Eliza; Kusumaningarti, Miladiah (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This research aims to determine the effect of cash flow and debt ratios on companies with financial performance as a moderating variable. This research uses quantitative methods. The data used is secondary data in the form of financial reports for manufacturing companies in the food and beverage sector that were listed on the IDX before the 2016-2018 COVID-19 pandemic and during the 2019-2021 COVID-19 pandemic. The sampling technique used was purposive sampling. The results showed that before the pandemic cash flow had a positive effect on firm value, while during the pandemic this study proved that cash flow had no effect on firm value. The ratio variable before the pandemic in this study proved a positive influence on firm value, while during the pandemic this study proved that the debt ratio had a positive effect on firm value. Based on the moderated cash flow equation variable, it shows that before and during the pandemic it proves that financial performance cannot moderate the effect of cash flow on firm value. And the moderated debt ratio variable before and during the pandemic proves that financial performance can moderate the effect of the debt ratio on firm value.